THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN THE FORMATION OF RELIGIOUS CHARACTER AMONG INMATES IN THE PAREPARE CITY CORRECTIONAL FACILITY - Zalzabila, Jumrana; Mahsyar, Mahsyar; Ahdar, Ahdar (FAJAR Jurnal Pendidikan Islam, 2025)
Islamic education in the Parepare Correctional Institution plays a crucial role in shaping the religious character of inmates. This study examines the implementation of religious education as a rehabilitation effort that focuses not only on cognitive aspects but also on moral and spiritual values. The methods used include interviews, observations, and documentation, with descriptive data analysis. The results indicate that religious activities, such as communal prayers and Quran recitations, successfully enhance the religious awareness of inmates. However, challenges such as staff competency and inmate boredom need to be addressed to achieve optimal outcomes. This study provides recommendations for developing more effective and innovative training programs to support the social reintegration of inmates.